2022
DOI: 10.3389/fbioe.2021.795425
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Copper-Based Biomaterials With Antibacterial and Osteogenic Properties for Bone Tissue Engineering

Abstract: Treating bone defects coupled with pathogen infections poses a formidable challenge to clinical medicine. Thus, there is an urgent need to develop orthopedic implants that provide excellent antibacterial and osteogenic properties. Of the various types, copper-based biomaterials capable of both regenerating bone and fighting infections are an effective therapeutic strategy for bone tissue engineering and therefore have attracted significant research interest. This review examines the advantages of copper-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Therefore, efforts are required to produce implants with antibacterial functions that reduce infection in orthopedics. 39 Due to its having no osteogenic activity, PI is incapable of forming an integration with host bone, which may increase the possibility of bacteria entering the micro-environment at the interface of the implant and bone, which potentially induces infection. 40 In this study, PI showed no antibacterial effect while SPM0 exhibited low antibacterial effect due to the presence of –SO 3 H groups with low antibacterial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efforts are required to produce implants with antibacterial functions that reduce infection in orthopedics. 39 Due to its having no osteogenic activity, PI is incapable of forming an integration with host bone, which may increase the possibility of bacteria entering the micro-environment at the interface of the implant and bone, which potentially induces infection. 40 In this study, PI showed no antibacterial effect while SPM0 exhibited low antibacterial effect due to the presence of –SO 3 H groups with low antibacterial effect.…”
Section: Discussionmentioning
confidence: 99%
“…The latest advances in copper (Cu)-based biomaterials with osteogenic and antibacterial properties in bone tissue engineering have been illustrated well by Shen et al [ 21 ]. According to the comprehensive review, adding Cu to complex hydroxyapatite-containing materials results in better bone substitutes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth recalling that silver is presently widely used in wound dressings and medical devices because it exerts broad-spectrum antimicrobial activity against Gram-positive and -negative bacteria, viruses, fungi, and protozoa [ 20 , 21 ], while copper is an esteemed antimicrobial agent and has long been used for its medical properties [ 22 , 23 ]. Nowadays, copper is widely studied in different forms and formulations for the antimicrobial treatment of surfaces [ 24 , 25 ] and on medical devices and implants [ 26 , 27 ]. We can find various examples of copper used in its metallic state [ 28 , 29 , 30 ], in a nanoparticle form [ 31 ], and as a coordination compound or ionic co-crystal [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%